A pharmacoeconomic approach to assessing the costs and benefits of air quality interventions that improve health: a case study. Issue 6 (21st June 2016) - Lomas, James; Schmitt, Laetitia; Jones, Sally; McGeorge, Maureen; Bates, Elizabeth; Holland, Mike; Cooper, Duncan; Crowther, Richard; Ashmore, Mike; Rojas-Rueda, David; Weatherly, Helen; Richardson, Gerry; et al.
Abstract : Objective: This paper explores the use of pharmacoeconomic methods of valuation to health impacts resulting from exposure to poor air quality. In using such methods, interventions that reduce exposure to poor air quality can be directly compared, in terms of value for money (or cost-effectiveness), with competing demands for finite resources, including other public health interventions. Design: Using results estimated as part of a health impact assessment regarding a West Yorkshire Low Emission Zone strategy, this paper quantifies cost-saving and health-improving implications of transport policy through its impact on air quality. Data source: Estimates of health-related quality of life and the National Health Service (NHS)/Personal Social Services (PSS) costs for identified health events were based on data from Leeds and Bradford using peer-reviewed publications or Office for National Statistics releases. Population: Inhabitants of the area within the outer ring roads of Leeds and Bradford. Main outcomes measures: NHS and PSS costs and quality-adjusted life years (QALYs). Results: Averting an all-cause mortality death generates 8.4 QALYs. Each coronary event avoided saves £28 000 in NHS/PSS costs and generates 1.1 QALYs. For every fewer case of childhood asthma, there will be NHS/PSS cost saving of £3000 and a health benefit of 0.9 QALYs. A single term, low birthweight birth avoided saves £2000 in NHS/PSS costs. Preventing a preterm birth saves £24 000 in NHS/PSS costs and generates 1.3 QALYs. A scenario modelled in the West Yorkshire Low Emission Zone Feasibility Study, where pre-EURO 4 buses and HGVs are upgraded to EURO 6 by 2016 generates an annual benefit of £2.08 million and a one-off benefit of £3.3 million compared with a net present value cost of implementation of £6.3 million. Conclusions: Interventions to improve air quality and health should be evaluated and where improvement of population health is the primary objective, cost-effectiveness analysis using a NHS/PSS costs and QALYs framework is an appropriate methodology.